Islamic Broadcasting Communication Students Need Analysis Based on Task-Based Language Teaching for ESP Curriculum Development - Abdur Rofik; Latifah Dwi Ariyani (Soshum: Jurnal Sosial dan Humaniora, 2023)
Islamic Broadcasting Communication students need certain experiences in learning English. English as a global language should be in line with their specific purposes. Therefore, it is essential to formulate students’ language skill experiences during their study in the Islamic Broadcasting Communication study program to find real benefits in EFL learning. The study is a Need Analysis (NA) which involves 30 students of the Islamic Broadcasting Communication study program, and 3 ESP lecturers of Universitas Sains Alqur’an, Central Java in Wonosobo, Indonesia. The aims are to investigate the students’ needs in ESP and to confirm if students’ needs in English lectures are reflected in the existing curriculum or not. The study is conducted using descriptive qualitative. The data are collected through a questionnaire, documentation, and interview. The study reveals that (1) the students of the study program need some changes to adapt to present needs in terms of ESP outcomes, task goals, preferred topics, setting, teacher and student roles, and media (2) the study promotes curriculum development as the provided curriculum does not accommodate students’ needs appropriately.